0058 Youtube As An Educational Tool: The Launch Of A Simulated Surgical Procedures Channel. (1st November 2014) - Yiasemidou, Marina; Glassman, Daniel; Tomlinson, James; Gough, Michael
Abstract : Background: Audiovisual technology is widely used in surgical education (1–2). Prior to the widespread use of social media, such materials were only available on a commercial basis. Subsequently "YouTube" has provided a medium for allowing unlimited, free access to educational videos (2). Thus, the School of Surgery has launched a simulation platform using this facility. The aims of this study were to assess the quality and educational value of the product and to seek trainees' views about the relative merits of e-learning. Methods: Fourteen videos of procedures included in our core surgery simulation programme were produced and uploaded to "YouTube". Each was linked to an online survey. Results: After a month, the channel had had >500 views. Ten trainees, two consultants, one research fellow and one staff grade doctor replied to our questionnaire (specialties: general surgery: 5, trauma and orthopaedics: 3, others: 6). Eleven out of fourteen, were working in the UK at the time of the survey. An equal number, were UK medical graduates and 12/14 had received postgraduate training in this country. All of the respondents reported that the commentary, length and quality of the videos was good and 10/14 found them relevant to their educational needs. 7/14 learnt a great deal and 13/14 would recommend them to a colleague. The most popular choice of e-learning resource was; videos of real procedures (42.9%), followed by illustrations/animations of surgical procedures (21.4%). Group tutorials and interactive sessions with experts were least favoured. Conclusion: A "YouTube" channel can be a valuable educational resource for surgical training. The quality of its content should be assessed and regulated by a specialty education lead. The future provision of e-learning modules should be guided by the opinions of the respondents. References: Surgical videos. http://www.nlm.nih.gov/medlineplus/surgeryvideos.html Al-Khatib TA. Surgical education on YouTube. Saudi Med J 2014;35(3):221–3